RANCANG BANGUN ALAT PENETAS TELUR AYAM BERBASIS MIKROKONTROLER - M Taufiq Tamam; Arif Johar Taufiq; Gunawan P B (Universitas Muhammadiyah Purwokerto, 2010)
Has done research on chicken egg incubator device based on microcontroller. This tool works by controlling the temperature in the hatching room, which is between 36 °C to 39 °C. Based on test results, the tool is able to hatch chicken eggs with a success rate to 60%. Key word: chicken egg incubator, microcontroller